2006
DOI: 10.21608/ejabf.2006.1899
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity and Bioaccumulation of Cadmium in the Freshwater Bivalve Corbicula Fluminalis Müller, 1774.

Abstract: ABSTRACThe influence of different concentrations of cadmium on Corbicula fluminalis was examined by a toxicity experiment. Acute toxicity was analyzed by measurement of the 96h. LC50 and daily survival rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…In various investigations the sensitivity of protozoa and other aquatic organisms to Cd(II) has been described, for example: Colpoda steinii (protozoa) of 0.5-5.0 mg.L -1 (Díaz et al, 2006), Tetrahymena owiformis (protozoa) of 3-10 mg.L -1 (Sauvant et al, 1995), D. magna (microcrustacean) of 0.004 mg.L -1 (Okamoto et al, 2015), Corbicula fluminalis (bivalve) of 0.52-0.56 mg.L -1 (Abdel-Gawad, 2006) and Channa punctatus (fish) of 5.2-8.4 mg.L -1 (Gupta & Rajbanshi, 1988). In contrast, it has been reported that the tolerance of protozoa to Cd(II) may be due to the following mechanisms: i) formation of granules resistant to higher concentrations of the element (Nilsson, 1981), which can contain several elements and function as structures involved in detoxification or regulation of metal ions (Dunlop & Chapman, 1981); ii) formation of a metallothionein related to stress regulation by PTE (Martín-González et al, 2006), where Cd induces a Cd-metallothionein tetramer similar in amino acid composition to metallothioneins from certain invertebrates and vertebrates (Piccinni et al, 1987).…”
Section: Toxicity Of Potentially Toxic Elements On Ciliated Protozoamentioning
confidence: 99%
“…In various investigations the sensitivity of protozoa and other aquatic organisms to Cd(II) has been described, for example: Colpoda steinii (protozoa) of 0.5-5.0 mg.L -1 (Díaz et al, 2006), Tetrahymena owiformis (protozoa) of 3-10 mg.L -1 (Sauvant et al, 1995), D. magna (microcrustacean) of 0.004 mg.L -1 (Okamoto et al, 2015), Corbicula fluminalis (bivalve) of 0.52-0.56 mg.L -1 (Abdel-Gawad, 2006) and Channa punctatus (fish) of 5.2-8.4 mg.L -1 (Gupta & Rajbanshi, 1988). In contrast, it has been reported that the tolerance of protozoa to Cd(II) may be due to the following mechanisms: i) formation of granules resistant to higher concentrations of the element (Nilsson, 1981), which can contain several elements and function as structures involved in detoxification or regulation of metal ions (Dunlop & Chapman, 1981); ii) formation of a metallothionein related to stress regulation by PTE (Martín-González et al, 2006), where Cd induces a Cd-metallothionein tetramer similar in amino acid composition to metallothioneins from certain invertebrates and vertebrates (Piccinni et al, 1987).…”
Section: Toxicity Of Potentially Toxic Elements On Ciliated Protozoamentioning
confidence: 99%